Julia Kisielewska (1874-1943) i jej wkład do praktyki i myśli pedagogicznej - Ewa Wiśniewska (Jagiellonian University Press, 2023)
Artykuł przedstawia sylwetkę Julii Kisielewskiej (1874‒1943) publicystki, krytyczki literackiej, nauczycielki i społeczniczki żyjącej oraz tworzącej na przełomie XIX i XX wieku. Zaprezentowano najistotniejsze fakty z jej życia, przypomniano twórczość literacką, działalność pedagogiczną i społeczną. Działalność ta rozwijała się na najwyższym poziomie. Jest autorką ponad stu pięćdziesięciu artykułów w czasopismach okresu Młodej Polski i dwudziestolecia międzywojennego, a także kilku podręczników do nauki historii w szkole. Była wybitną nauczycielką, organizatorką i społeczniczką. Pracowała w szkołach żeńskich rożnego typu. Przez dwadzieścia lat kierowała szkołami żeńskimi w Płocku. Ówcześnie była osobą znaną i szanowaną. Niestety, dziś Julia Kisielewska pozostaje praktycznie zapomniana pomimo ciekawej biografii i wyjątkowej pracy. Julia Kisielewska (1874‒1943) and Her Contribution to Pedagogical Practice and Thought The article presents the profile of Julia Kisielewska (1874‒1943), a publicist, literary critic, teacher and social worker, who lived and worked at the turn of the 19th and 20th centuries. Moreover, the study shows the most important facts from her life, literary work, as well as pedagogical and social activities. Her journalistic and teaching activity was developed at the highest level. She is the author of over one hundred and fifty publications in magazines of the Young Poland and the interwar period, as well as several textbooks for teaching history at school. She was an eminent teacher, organizer and social worker. Kisielewska worked in girls' schools of various types. For twenty years, she managed schools for girls in Płock. At that time, she was a well-known and respected person. Unfortunately, today Julia Kisielewska remains practically forgotten despite her interesting biography and rich legacy.